Essor du maraîchage à visée uniquement locale dans le Pharak, région touristique de l’Everest, Népal - Abadia Céline; Aubriot Olivia; Smadja Joëlle; Vaillant Michel; Oswald Marc (Revue de Géographie Alpine)
Pharak region, traversed by the Everest trekking route, sees thousands of hikers every year who come to discover the Khumbu high-mountain landscapes. Formerly a land of pasture, this region has been the scene of significant socio-economic changes since the early 1970s. The population, mainly Sherpa, is gradually abandoning agro-pastoral activities to become more involved in the tourism industry. By generating economic benefits, creating demand and capturing a portion of the labour force, tourism is engendering important transformations in agriculture in the region. Trade exchanges are on the increase and we are witnessing a reconfiguration of the agrarian landscape according to market opportunities. Market gardening, in particular, is gaining momentum and is the subject of a new local business. Based on this example, this article aims to highlight the originality of this way of exploiting the environment, which has developed along with the growth of tourism, yet independently of urban growth and road construction.